Do Parents Synchronise Nest Visits as an Antipredator Adaptation in Birds of New Zealand and Tasmania? - Khwaja, Nyil; Massaro, Melanie; Martin, Thomas E.; Briskie, James V. (Frontiers in Ecology and Evolution, 2019)
Birds with altricial offspring need to feed them regularly, but each feeding visit risks drawing attention to the nest and revealing its location to potential predators. Synchronisation of visits by both parents has been suggested as a behavioural adaptation to reduce the risk of nest predation. Under this hypothesis, higher risk of nest predation favours greater synchrony of parental feeding visits. We investigated this prediction over three timescales using nestling provisioning data from 24 passerine species in Tasmania and New Zealand. We estimated the extent to which parents actively synchronised their visits to the nest by comparing observed patterns of synchrony with those expected to occur at random. We found that in general, species did not synchronise visits more often than expected by chance. Species varied in the tendency to synchronise visits, but this variation was not explained by likely predation pressure in the distant evolutionary past: New Zealand endemic species, which evolved in the absence of mammalian nest predators, synchronised their visits as often as species which evolved with more diverse predatory guilds. Nest predation risk has increased over time in New Zealand due to introduced predators, but synchrony in visits also was not explained by manipulated predation risk: visit synchrony was equivalent between a predator-removal site and a site where predators remained. However, within one New Zealand species, visit synchrony was higher for mainland populations, which have been exposed to predatory mammals for c.800 years, than for a population on an offshore island to which predatory mammals were never introduced. We conclude that breeding birds may have some capacity to adapt the synchrony with which they provision over short evolutionary timescales. However, the lack of synchrony in most species suggests that either asynchrony provides benefits that outweigh the greater risk of predation, or synchrony incurs costs not compensated by reduced predation.